Drudgery Reduction for Farm Women: An Ergonomic Assessment of Improved Agricultural Tools and Implements - Singh, Premlata; Singh, Jogender; Rahul, (Indian Journal of Extension Education, 2011)
In spite of technological advancements, there are hardly any deliberate efforts made to generate women friendly technologies to increase their efficiency and effectiveness and reduce drudgery. It is paradox in the context that farm women account for more than 90 percent of agricultural work force and 75 percent of female population is engaged in agriculture (Census 2001, GOI). Such a large work force is associated in the field but are still being deprived of the benefits of farm mechanization in order to minimize their health risk and drudgery. Ergonomics of tools and implements can give interfaces for better design of equipment in order to increase efficiency without jeopardizing health. A comparative study was conducted for some selected agricultural implements to evaluate cardio vascular load, energy expenditur, yield, perceived exertion and musculo-skeletal problems in use of traditional as well as improved tools, viz., weeders, sickle, cleaner grader, fertilizer broadcaster and bhindi plucker. Percentage reduction in cardio- vascular rate and energy expenditure for the above tools was 1.85, 3.47, 6.66, 12.53; 16.40, 32.40; 4.87, 11.32; and 7.60, 13.17, respectively. The findings revealed that application of improved tools in agricultural operation, not only reduces drudgery of farm women but also aims at higher economic production. However, variations were observed depending upon the design of the tools.